(untitled) (TERRA LATINOAMERICANA, 2025)
One of the most important and widely produced crops in the world is lettuce (Lactuca sativa L.), due to its high nutritional value and organoleptic properties. However, the abuse of chemical fertilizers for its production results in soil erosion and aquifers pollution. The purpose of our study was to evaluate the ef fect of organic fertilizers on the post-harvest quality of lettuce (Lactuca sativa L.) at 5 °C. A completely randomized experimental design was developed, involving romaine lettuces (Lactuca sativa L. var. longifolia) grown under 3 dif ferent treatments: Chemical fertilizer (FQ); cof fee pulp vermicompost (LC); and sheep manure vermicompost (LHB), with 10 replicates of each treatment. Af ter harvest, the lettuces were stored at 5±1 °C. Selected quality parameters of total soluble solids (TSS), pH, color, total phenolic compounds, total flavonoids, in vitro antioxidant activity, and polyphenol oxidase (PPO) activity were assessed on days 0, 5 and 10 of storage. The results showed that by the end of storage, LC lettuces had the highest luminosity and chromaticity values, as well as total phenolic compounds (0.9 mg EAG g-1), total flavonoids (0.8 mg CE g-1), DPPH antioxidant activity (4.1 uET g-1) and FRAP antioxidant activity (6.9 uET g-1 μTE g-1). LHB lettuces showed the lowest PPO activity. These results show evidence that the use of organic fertilizers, especially cof fee pulp vermicompost, improves the postharvest quality of lettuce and maintains its shelf-life for up to 10 days of storage at 5±1 °C, which can contribute to prevent spoilage and wastes, as well as to substitute the use of inorganic fertilizers, with their detrimental environmental ef fects.